The Cropping of Edgar Degas’ Place de la Concorde: Vandalism or Innovation? - Demina, Natalia B. (Actual Problems of Theory and History of Art, 2020)
Edgar Degas’ painting Place de la Concorde (1876. The State Hermitage Museum, St. Petersburg) is an extraordinary example of a daring composition. In 1995 Albert Kostenevich pointed out that a strip of original canvas some 4 cm wide, with original painting on it, had been folded under the lower strut of the stretcher. In 2012 he suggested that it had been done for some unknown reason by Count Lepic, first owner of the painting, after the cropping of the lower edge of the painting. This paper suggests that it was the artist himself who was responsible for cropping the painting.Among the arguments put forward by Albert Kostenevich was the lack of a signature on Place de la Concorde, although Degas is known to have signed and dated the works he intended to sell. But Degas did not always sign paintings he parted with, notably portraits. Nor are there any documents to indicate that Degas sold Place de la Concorde to Lepic. Moreover, nowhere in the published correspondence between Durand-Ruel, the owner of the painting, his clients and the artist, is there any mention that the painting had been in any way cropped or adjusted. This all indicates that its format was that chosen by the author.Other arguments in favour of the author’s own alteration of his composition is that it seems strange thatthe owner of a family portrait would decide to cut it back, particularly if the cropping affected the figures offamily members. Such a barbarous act might also threaten the collapse of the friendship.The most important argument lies in the painting itself: some of the final touches in black paint finish right on the line of the fold, evidence that Degas put the final strokes on the canvas after he himself had altered the canvas size and then fixed it on the stretcher. X-rays reveal that Degas altered the composition of Place de la Concorde during the process of work and his radical cropping of the canvas may be considered the penultimate alteration. Thus, we are dealing not with some barbarous act by Сount Lepic, but with an innovative gesture as Degas sought the boldest compositional solution.
Keywords: Edgar Degas; Place de la Concorde; Lepic; Durand-Ruel; compositional alteration; conservation; The State Hermitage Museum